Protection from gamma-radiation insult to antioxidant defence and cellular DNA by POLY-MVA, a dietary supplement containing palladium-lipoic acid formulation. (12th October 2009) - Menon, Aditya; Krishnan, Chirakkal V.; Nair, Cherupally Krishnan Krishnan
Whole-body exposure to gamma radiation was found to result in damage to cellular DNA and lowering of antioxidant levels in various tissues. Administration of POLY-MVA, a palladium-lipoic acid formulation, for seven days prior to whole body gamma radiation significantly reduced the damage to cellular DNA in bone marrow and blood leukocytes, as well as preventing the radiation-induced lowering of tissue antioxidant levels.